SYNTHESIS UiO-66 ON MESOPOROUS SILICA SUPPORT - Arfyanti Fajrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2016)
Zirconium-benzenedicarboxylate or UiO-66, has been synthesized by the method solvothermal using ZrCl4 reactant and the acid 1,4-benzendikarboksilat with the solvent DMF at 120 ̊ C for 24 hours. In addition UiO-66 is also synthesized by supporters of mesoporous silica (UiO-66/MCM-41) using the same method with mesoporous silica mass variation of 50, 100, and 200 mg. The solids obtained were characterized by XRD, FTIR, SEM-EDX, TGA, and nitrogen adsorption-desorption. All the materials have been synthesized have diffractogram peaks at angles 2θ = 7,4 ̊ and 8,5 ̊ with different intensity and widening the intensity UiO-66. Material UiO-66 and UiO-66/MCM-41 has a similar morphology, namely small dots are clustered. All the material shows thermal stability between 455-513 ̊ C with a specific surface area UiO-66 (497 m2/g) lower than UiO-66/MCM-41(50) (614 m2/g) and UiO-66/MCM- 41(200) 548 m2/g.